(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: Hepatitis C virus (HCV) is a single-strand, positive sense ribonucleic acid (RNA) virus belonging to the flaviviridae family. Treatment of hepatitis C with interferon- ribavirin combination therapy has proved to be effective in terms of biochemical and virological response. Retinopathy (Retinal changes) is a well-recognized side effect of interferon therapy. Cases have been reported where patient of chronic hepatitis C being treated with interferon suffered from blindness. The objective of the study is to determine the retinal changes in patients of chronic hepatitis C who are on conventional interferon alpha- ribavirin combination therapy. Design: Descriptive case series. Place and duration of study: The study was conducted in Hepatitis Clinic, Medical Unit III Services Hospital Lahore. The study was carried out over a period of six months, from 25th August 2010 to 25th Feb. 2011. Method: One hundred and fifty were included in the study. Interferon and ribavirin combination therapy was then started in the dose of 3 million units subcutaneously thrice a week and 400mg orally thrice a day respectively. Fundoscopy was done by a single ophthalmologist in every patient after the week 6 and 12 of the start of therapy. The presence or absence of retinopathy with the detail of retinal changes was documented. Results: One hundred and fifty patients were enrolled in the study. Eighty eight patients (58.7%) were male and 62 (41.3%) female. One hundred and sixteen patients (77.3%) did not develop any retinal changes but remaining 34 patients (22.7%) suffered from retinopathy. Out of the total 34 patients who developed retinopathy, 13 patients (38.2%) had it in the form of retinal haemorrhages and 21 patients (61.8%) developed cotton wool spots. No patient suffered from macular oedema. Conclusion: It is concluded that every patient on interferon therapy should have regular eye examination for surveillance of retinopathy to prevent blindness, a dreadful consequence